2022
DOI: 10.3390/antibiotics11070934
|View full text |Cite
|
Sign up to set email alerts
|

Infections in G6PD-Deficient Hospitalized Patients—Prevalence, Risk Factors, and Related Mortality

Abstract: G6PD deficiency is a genetic disease that weakens the immune system and renders affected individuals susceptible to infections. In the Sultanate of Oman resides a high number of recorded G6PD cases due to widespread consanguineous marriage, which may reach 25% of the population. We studied the infection patterns and risk factors for mortality to provide antimicrobial stewardship recommendations for these patients. After obtaining ethical approval, a registry of recorded cases was consulted retrospectively to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Our patient presented with a known G6PD deficiency in correspondence to additional potential undiagnosed immunodeficiencies, which ultimately could have served as a significant risk factor for disseminated coccidioidomycosis in the form of CM. G6PD deficiency can lead to reduced nicotinamide adenine dinucleotide phosphate oxidase activity in phagocytes, resulting in immunodeficiency, and can lead to bacterial, viral, and fungal infections [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient presented with a known G6PD deficiency in correspondence to additional potential undiagnosed immunodeficiencies, which ultimately could have served as a significant risk factor for disseminated coccidioidomycosis in the form of CM. G6PD deficiency can lead to reduced nicotinamide adenine dinucleotide phosphate oxidase activity in phagocytes, resulting in immunodeficiency, and can lead to bacterial, viral, and fungal infections [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cases with severe G6PD deficiency and infections have rarely been reported; however, this figure may be an underestimate. A recently published study focused on infection in hospitalized patients with G6PD deficiency ( Alrahmany et al, 2022 ). Only 620 of 3,334 registered G6PD-deficient patients did not have any microbiological cultures or hospitalization details.…”
Section: Discussionmentioning
confidence: 99%
“…The G6PD enzyme stimulates the reduction in nicotinamide adenine dinucleotide phosphate (NADP) in the pentose phosphate pathway (PPP) to generate NADPH; the latter is a substrate for NADPH oxidase responsible for regenerating the antioxidant glutathione that protects the blood cells against oxidative stress. The deficiency of G6PD leads to premature loss of cell integrity under the stress of sulfa-containing drugs, certain foods, and systemic infections, which explains why many studies suggested G6PD deficiency to be a significant predictor of hospitalization and severe infections [ 3 , 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies identified a slew of life-threatening infections in G6PD-deficient patients, with bacteremia, respiratory, cerebrospinal, and urinary tract infections being the most common. Gram-negative bacteria were the predominant cause of these infections, followed by Gram-positive bacteria and, to a lesser extent, a variety of fungi and viruses [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation